Risk-sharing agreements for high cost medicines in Chile - Poblete, Sergio (Journal Studies of Public Policy, 2020)
The objective of this article is to characterize and analyze the risk-sharing agreements proposed by the pharmaceutical industry to achieve coverage under the Financial Protection System for High Cost Diagnostics and Treatments in Chile (Ricarte Soto Law). Through a review of the literature on the subject, a taxonomy of risk-sharing agreements was elaborated, identifying the advantages and disadvantages of each type from the perspective of public health policies. Findings show that most of the offers received considered financial agreements, mainly price discounts. To a lesser extent, bonification and portfolio discount also stand out for their frequency. It is important to note that the case analyzed is one of the first formal experiences of requesting risk-sharing agreements in the Chilean public health sector. However, the design and implementation of these contracts require a more proactive role of the public buyer. This demands the development of skills and infrastructure in the public health sector that allow the measurement of the performance of health technologies in practice.